Design and performance analysis of a single-drive axially-controlled miniaturized bearingless motor - Rubio, Guilherme Cavalcante (2018)
Some systems like blood pumps and equipment positioned in space stations or high towers require electrical machines with highly reliable operation and extended durability. Mechanical contact between rotating and static parts are a major cause of failure in electrical machines. To eliminate mechanical contact completely, magnetic bearings rose as an alternative to the usual mechanical ones. Through use of permanent magnets and electromagnets, it became possible to levitate the rotating parts, addressing the wearing and durability problems, at the expense of an increase in complexity of operation. In this kind of machine, miniaturization becomes more challenging. Position control structures are included and highly stable positioning is required. Each fraction of millimeter can lead the rotor shaft to contact with the stator. By adapting the mechanical structure and electromagnetic parameters of a bearingless motor, it was possible to optimize flux density distribution and increase torque in a miniaturized permanent magnet synchronous motor, while keeping position stability high. This dissertation presents the method employed and the intermediate steps taken towards the final version, as well the finite element analysis results.